Metabolomic signatures associated with depression and predictors of antidepressant response in humans: A CAN-BIND-1 report - Giorgia Caspani (Nature Portfolio, 2021)
Caspani et al. report on sex-specific plasma lipoproteins predictive of response to two commonly used antidepressants. The authors show that lipoproteins belonging to the same main class but differing in size and density exhibit distinct associations with depression and with response to pharmacotherapy, highlighting the importance of evaluating lipoprotein subclass in depression research.